Technological Societies as a Basis for Socio-Political Changes in Philosophical Discourse - F. P. Furman (Управленческое консультирование)
Modern approaches to the development of information and communication technologies, the General level of their use can lead to the emergence of innovative tools of civil influence — digital activity associated with the level of civic readiness of the network environment and properly selected digital tools: used social services, promotion technologies and national ideas in the practice of its implementation of modern society.. A significant indicator of the overall readiness of the network environment for significant changes in the conditions of globalization and the increasing role of national identity is the presence of network structures of developers and the degree of their involvement in the network of increased civic activity, which can contribute to the system of significant socio-political changes.